The level of Jordanian citizen’s awareness of the social responsibility standards in light of the Corona pandemic (Covid-19) - Tarwaneh, Amane Wahed; Alsuhimat, Fadi Mohammad; As'ad, Ameera Mohammad (Journal of Educational and Psychological Sciences, 2020)
The aim of the current research is to know the level of Jordanian citizen’s awareness of social responsibility standards in light of the Corona epidemic, in order to achieve this objective the research followed the descriptive analytical approach through developing a scale that was distributed to the individuals of the study sample which was chosen in the stratified random method and reached (384) individuals, a total of (324) questionnaires were retrieved and valid for statistical analysis. The results of the research showed that the level of Jordanian citizen’s awareness of social responsibility standards in light of the Corona epidemic came in a moderate degree and that there were no differences in the estimates of the study sample towards the level of Jordanian citizen’s awareness of social responsibility standards in light of the Corona epidemic due to the variables (gender, job, age). The research has come out with a set of recommendations, including the need to increase awareness of the Jordanian citizen of the importance of social responsibility and its great role in helping Jordanian society to achieve economic and social stability, the need for the Jordanian government to be alert and the decision-makers to focus on the importance of social responsibility for members of Jordanian society.